Factors affecting evidence-based practice in nursing education in Hainan, China - Siyuan, Huang; Vijayaratnam, Phawani; Muthukrishnan, Priyadarshini; Permal, Shalini; Mary, Irudhaya (International Journal of Innovative Research and Scientific Studies, 2025)
With medical industry advancements, nurses must ensure patient safety and high-quality care through accurate clinical decision-making. However, in areas like Hainan, where medical resources are relatively scarce, nurses’ clinical decisions come from evidence-based practice. Nurses usually rely on work experience and existing professional knowledge to formulate nursing plans. It is crucial for Hainan to achieve better medical care, especially in the use of evidence-based nursing education to improve nurses’ evidence-based practice capabilities. This study employed quantitative methods and distributed questionnaires to 354 nurses across three affiliated hospitals of Hainan Medical University. Previous studies utilizing the Tony Bush Institute model have indicated that nurses’ professional knowledge, critical thinking, and teamwork significantly and positively impact the implementation of evidence-based practices. The study promotes the development of evidence-based nursing education in Hainan by improving professional knowledge cultivation under the collegial model [1]. Cultivating nurses’ critical thinking and strengthening teamwork provide a practical basis for improving nurses’ evidence-based practice capabilities. This will not only help improve the overall medical level of Hainan and benefit patients and medical service providers but also contribute to the realization of the United Nations Sustainable Development Goals 3 (good health and well-being) and 4 (quality education).